(3x-1)(2x+1)=0

Simple and best practice solution for (3x-1)(2x+1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-1)(2x+1)=0 equation:


Simplifying
(3x + -1)(2x + 1) = 0

Reorder the terms:
(-1 + 3x)(2x + 1) = 0

Reorder the terms:
(-1 + 3x)(1 + 2x) = 0

Multiply (-1 + 3x) * (1 + 2x)
(-1(1 + 2x) + 3x * (1 + 2x)) = 0
((1 * -1 + 2x * -1) + 3x * (1 + 2x)) = 0
((-1 + -2x) + 3x * (1 + 2x)) = 0
(-1 + -2x + (1 * 3x + 2x * 3x)) = 0
(-1 + -2x + (3x + 6x2)) = 0

Combine like terms: -2x + 3x = 1x
(-1 + 1x + 6x2) = 0

Solving
-1 + 1x + 6x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-1 + -2x)(1 + -3x) = 0

Subproblem 1

Set the factor '(-1 + -2x)' equal to zero and attempt to solve: Simplifying -1 + -2x = 0 Solving -1 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -2x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -2x = 0 + 1 -2x = 0 + 1 Combine like terms: 0 + 1 = 1 -2x = 1 Divide each side by '-2'. x = -0.5 Simplifying x = -0.5

Subproblem 2

Set the factor '(1 + -3x)' equal to zero and attempt to solve: Simplifying 1 + -3x = 0 Solving 1 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -3x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -3x = 0 + -1 -3x = 0 + -1 Combine like terms: 0 + -1 = -1 -3x = -1 Divide each side by '-3'. x = 0.3333333333 Simplifying x = 0.3333333333

Solution

x = {-0.5, 0.3333333333}

See similar equations:

| x=1287.4(2017)+48470 | | 10(s-4)=-146 | | =31x-18y | | (2x^2-3x^3)-(9x^2-5x^3)=0 | | 100000=1287.4x+48470 | | (2x^2-3x^3)(9x^2-5x^3)=0 | | 22-3x=2 | | 18-2(5-3x)=-5x-3 | | (2x^2-3x^3)(9x^2-5x^3)= | | 4(d-8)+3= | | (4x-13y)-(-27x+5y)= | | 3(x+4)+3=-5(x-8)-1 | | 6(t+4)=-6 | | 7(r+9)= | | 10-48x-12=27x+36x | | 6w-w+5w= | | (16-10)x-35000=0 | | 5x(3-13)=100 | | 7(3s+10)=238 | | 10x+8=4x+3 | | 2(2l+2)=24 | | 8x-32=5+10x | | -3(2t+9)=-57 | | (2y+2)*350=(0.6y+6)*350 | | 8x^3-30x^2+48=0 | | 2a+9=8a-9 | | 4(a-4)=16 | | 5(f-3)=-35 | | 10(s-3)=-58 | | 9x-3x=2x+20 | | 4x-(2x-8)=5(1+2x) | | 0.5x-7=3.9x-24 |

Equations solver categories